The effect of nano-TiO2 addition on Portland cement properties - Thanongsak Nochaiya (2018)
This study describes the effects of nano-TiO2 (photocatalyst) on Portland cement pastes properties such as compressive strength and hydration. The water-cement ratio of 0.5 was used to produce in both mortars and pastes sample. No detrimental effect was found on compressive strength but there was a slightly increase in the density. Furthermore, hydration phases and microstructure characterization were carried using thermal gravimetric (TGA) technique and scanning electron microscope (SEM) analysis. ©2010 IEEE.